Welsh newspapers online - National Library of Wales (2017)
Welsh Newspapers Online is a free online resource from the National Library of Wales where you can discover millions of articles from the Library’s rich collection of historical newspapers.Welsh Newspapers Online currently lets you search and access over 1,100,000 pages from nearly 120 newspaper publications generally up to 1910.